STRUCTURE ANALYSIS OF ENGLISH ABSTRACTS IN INTERNATIONAL JOURNAL PUBLISHED IN 2020 - Tira Nur Fitria (Universitas Bunda Mulia, 2021)
The objective of this research is to analyze the move structure of English abstracts published in the International Journal of Economics, Business, and Accounting Research (IJEBAR) in 2020. The result shows that 10 types of moves were used in 96 abstracts’ articles in the IJEBAR journal. The abstracts’ article used two, three, or four moves. The first type was M2-M3-M4 (Purpose-Method-Product/Result) which shows 3 moves. It consists of 49 articles (51.04 %). The second type is M1-M2-M3-M4 (Introduction-Purpose-Method-Product/Result) which shows 4 moves. It consists of 27 articles (28.13 %). The third type is M2-M3-M4-M5 (Purpose-Method-Product/Result-Conclusion) shows 4 moves. It consists of 6 articles (6.25 %). The fourth type is M1-M2-M4 (Introduction-Purpose-Product/Result) which shows 3 moves. It consists of 4 articles (4.17 %). The fifth type is M1-M2-M3-M4-M5 (Introduction-Purpose-Method-Product/Result-Conclusion) which shows 5 moves. It consists of 3 articles (3.12%). The sixth type is M1-M3-M4 (Introduction-Method-Product/Result) which shows 3 moves. It consists of 3 articles (3.12 %) The seventh type is M1-M4 (Introduction-Product/Result) which shows 2 moves. It consists of 1 article (1.04 %). The eighth type is M1-M3-M4-M5 (Introduction-Method-Product/Result-Conclusion) which shows 4 moves. It consists of 1 article (3.12 %). The ninth type is M2-M4 or Purpose-Product/Result which shows 2 moves. It consists of 1 article (1.04 %). The last type is M2-M5 (Purpose-Conclusion) which consists of 1 article (1.04 %). From the explanation above, it shows that the most frequent move uses 3 moves with type M2-M3-M4 or Purpose-Method-Product/Result.